2016
DOI: 10.1038/srep34116
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between cognitive performance and retinal nerve fibre layer thickness is largely explained by genetic factors

Abstract: Retinal nerve fibre layer (RNFL) thickness has been associated with cognitive function but it is unclear whether RNFL thinning is secondary to cortical loss, or if the same disease process affects both. We explored whether there is phenotypic sharing between RNFL thickness and cognitive traits, and whether such sharing is due to genetic factors. Detailed eye and cognitive examination were performed on 1602 twins (mean age: 56.4 years; range: 18–89) from the TwinsUK cohort. Associations between RNFL thickness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…It is known that the retina forms as a functional extension of the central nervous system, developing as a result of diencephalic evagination of pluripotent cells during embryogenesis [ 15 ]. In many cross-sectional studies, the RNFL has been shown to be thinner in people with memory loss and cognitive decline due to certain neurodegenerative disorders, such as AD and MS [ 6 9 ]. There is also some controversy regarding the effect of lens opacity on signal detection in OCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the retina forms as a functional extension of the central nervous system, developing as a result of diencephalic evagination of pluripotent cells during embryogenesis [ 15 ]. In many cross-sectional studies, the RNFL has been shown to be thinner in people with memory loss and cognitive decline due to certain neurodegenerative disorders, such as AD and MS [ 6 9 ]. There is also some controversy regarding the effect of lens opacity on signal detection in OCT.…”
Section: Discussionmentioning
confidence: 99%
“…The average RNFL thickness loss in patients with AD is 11 μm; in patients with MS, it is 7 μm. However, it is unclear whether the main ocular biomarker of RNFL thinning investigated for AD and MS is secondary to cortical loss (retrograde damage), or if the same disease process affects both the brain and the retina [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is extensive variation in testing for cognitive function even in different studies regarding the correlation to ophthalmological neuro-anatomy. 6,7,14,16,17 By exploring the data of the NFBC Eye Study we were able to find statistically significant correlations between the ONH parameters and surrogates for cognition: A higher education level and a faster HFA were associated with larger disc areas. These same correlations have been reported in the Beijing Eye Study.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we did not account for genetic factors that may contribute to retinal morphometric measures. For example, Jones-Odeh et al (2016) examined a large cohort of twins in the United Kingdom and learned that RNFL thickness was highly heritable (82%). Markers of vascular health in the retina have also been previously linked to neuropsychological functioning at midlife should be accounted for in future research (Shalev et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although emerging evidence points to the utility of OCT as a neuroimaging technique, only a limited number of studies have examined retinal morphometric measures and cognitive function. RNFL thickness has been positively associated with performance on the mini mental state examination among a large cohort of twins between 18 and 89 years (Jones-Odeh et al, 2016). Total macular volume and RNFL have also been associated with verbal intelligence and IQ among persons with MS (Ashtari et al, 2015).…”
Section: Introductionmentioning
confidence: 99%